Reorganization of the host epigenome by a viral oncogene - Ferrari, Roberto; Su, Trent; Li, Bing; Bonora, Giancarlo; Oberai, Amit; Chan, Yvonne; Sasidharan, Rajkumar; Berk, Arnold J.; Pellegrini, Matteo; Kurdistani, Siavash K.

(untitled) (Genome Research, 2012)
Adenovirus small e1a oncoprotein causes ∼70% reduction in cellular levels of histone H3 lysine 18 acetylation (H3K18ac). It is unclear, however, where this dramatic reduction occurs genome-wide. ChIP-sequencing revealed that by 24 h after expression, e1a erases 95% of H3K18ac peaks in normal, contact-inhibited fibroblasts and replaces them with one-third as many at new genomic locations. The H3K18ac peaks at promoters and intergenic regions of genes with fibroblast-related functions are eliminated after infection, and new H3K18ac peaks are established at promoters of highly induced genes that regulate cell cycling and at new putative enhancers. Strikingly, the regions bound by the retinoblastoma family of proteins in contact-inhibited fibroblasts gain new peaks of H3K18ac in the e1a-expressing cells, including 55% of RB1-bound loci. In contrast, over half of H3K9ac peaks are similarly distributed before and after infection, independently of RB1. The strategic redistribution of H3K18ac by e1a highlights the importance of this modification for transcriptional activation and cellular transformation as well as functional differences between the RB-family member proteins.